2012
DOI: 10.1002/ajmg.b.32087
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide association analysis of eating disorder‐related symptoms, behaviors, and personality traits

Abstract: Eating disorders (EDs) are common, complex psychiatric disorders thought to be caused by both genetic and environmental factors. They share many symptoms, behaviors, and personality traits, which may have overlapping heritability. The aim of the present study is to perform a genome-wide association scan (GWAS) of six ED phenotypes comprising three symptom traits from the Eating Disorders Inventory 2 [Drive for Thinness (DT), Body Dissatisfaction (BD), and Bulimia], Weight Fluctuation symptom, Breakfast Skippin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
5

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 50 publications
(60 reference statements)
0
51
0
5
Order By: Relevance
“…Twelve out of 14 variants previously reported to be associated with eating disorder-related symptoms, behaviors, and personality traits 59, 60 were found in our discovery meta-analysis and 7 had the same direction of effect (P=0.774) (Table S10), with one SNP (inside RUFY1 ) having P<0.05 (binomial P=0.459). We did not find evidence for signal enrichment in the 60 independent SNPs found in the Psychiatric Genomics Consortium data for ADHD, schizophrenia, bipolar disorder, or major depressive disorder 63-66 (Table S11).…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Twelve out of 14 variants previously reported to be associated with eating disorder-related symptoms, behaviors, and personality traits 59, 60 were found in our discovery meta-analysis and 7 had the same direction of effect (P=0.774) (Table S10), with one SNP (inside RUFY1 ) having P<0.05 (binomial P=0.459). We did not find evidence for signal enrichment in the 60 independent SNPs found in the Psychiatric Genomics Consortium data for ADHD, schizophrenia, bipolar disorder, or major depressive disorder 63-66 (Table S11).…”
Section: Resultsmentioning
confidence: 84%
“…Only two SNPs, rs1523921 (also found to be suggestively associated in the main case-control analysis) and rs10777211 located 333kb upstream of ATP2B1 , showed association at the 10 -5 significance level (Table S6). Similarly, subsequent analyses pertaining to associated phenotypes (weight regulation: BMI/obesity loci, 40, 61, 69, 70 and loci for extreme obesity; 61, 71, 72 psychiatric comorbidities: ADHD, schizophrenia, bipolar disorder, and major depressive disorder) or previous equivocal association findings for AN or eating disorders (AN variants, 42 eating disorder related symptoms, behaviors, and personality traits variants 59, 60 ) did not reveal significant findings. More adequately powered analyses that could allow us to detect variants that can distinguish between these two subtypes could be clinically meaningful in predicting clinical course and outcome and eventually in designing targeted therapeutics.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…A recent negative two-stage GWAS meta-analysis for AN in 5,551 cases and 21,080 controls concluded that the accrual of large genotyped AN case-control samples should be an immediate priority for the field to identify AN-predisposing genes [81]. Although there were no genome-wide significant hits reported, 72 independent markers with the lowest p values were selected for replication in an independent sample, and 76% of these loci produced results directionally consistent with the discovery sample [82].…”
Section: Genome-wide Association Studiesmentioning
confidence: 99%
“…For example, a GWAS study of eating disorder-related phenotypes found very weak signals; however, some of these had been implicated in previous studies [24].…”
Section: Genesmentioning
confidence: 99%